IMPLEMENTATION OF FUNDRAISING AND INCUBATION SYSTEM TO ACTUALIZE STUDENTS’ ENTREPRENEURIAL IDEAS THROUGH INDEKITA - Maulana, Danis; Handrioka, Herfian; Safitri, Karunia Eka; Karyatiningsih, Ulfa (Jurnal Entrepreneur dan Entrepreneurship, 2018)
Indekita provides social website page as a place to write concept of ideas to invite Indonesia’s young generation, especially students of each area in Indonesia, to act their ideas. Indekita has two concepts, namely fundraising and incubation. Programs include in incubating concept take form of discussion community, which invites many parties to criticize and advise in entrepreneurial ideas, and brings together many young innovators with mentors who can help provide insight about product development and competitiveness as well as opportunities in society. The concept of crowdfunding is fund raising with a joint venture or donation system online that will be done to fund students’ business concept. The implementation of fundraising system and business incubation through indekita.com can be realized by focusing ideas on innovative entrepreneurial business. With these two concepts, students are expected to obtain funds and develop their business concepts so as to create business that enhances community competitiveness and provides new job opportunities in each region through entrepreneurship.